Simplify each expression (a) \( \left(\frac{2}{y}\right)^{3}\left(\frac{3}{y}\right)^{2} \) (b) \( \left(\frac{b^{-4}}{a^{-4}}\right)\left(\frac{b}{a}\right)^{4} \) \( \square \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To simplify the first expression \( \left(\frac{2}{y}\right)^{3}\left(\frac{3}{y}\right)^{2} \), we can calculate each part separately. 1. \( \left(\frac{2}{y}\right)^{3} = \frac{2^3}{y^3} = \frac{8}{y^3} \) 2. \( \left(\frac{3}{y}\right)^{2} = \frac{3^2}{y^2} = \frac{9}{y^2} \) Now, multiplying these two results gives: \[ \frac{8}{y^3} \cdot \frac{9}{y^2} = \frac{8 \cdot 9}{y^{3+2}} = \frac{72}{y^5} \] For the second expression \( \left(\frac{b^{-4}}{a^{-4}}\right)\left(\frac{b}{a}\right)^{4} \): 1. Simplifying the first part: \(\frac{b^{-4}}{a^{-4}} = b^{-4} \cdot a^{4} = \frac{a^4}{b^4}\) 2. The second part calculates to: \(\left(\frac{b}{a}\right)^{4} = \frac{b^4}{a^4}\) Now, multiplying these two results gives: \[ \frac{a^4}{b^4} \cdot \frac{b^4}{a^4} = \frac{a^4 b^4}{b^4 a^4} = 1 \] So the complete simplified expressions are: (a) \( \frac{72}{y^5} \) (b) \( 1 \)